(untitled) (New York, 2009)
Annual editions: Criminal Justice 08/09 strives to maintain currency in matters of concern by providing upto date commentaries, reports and statistics from the most recent literature in the criminal justice field.
Keywords: Criminal justice,Hình sự tư pháp